(untitled) (Journal of Applied Learning and Teaching, 2025)
The effects of the direct and indirect relationships of academic performance, motivation, learning approach, course perceptions, academic background, personality, learning environment and prior learning are studied here. The analysis is conducted using Structural Equation Modelling (SEM), allowing for a comprehensive examination of these complex relationships within the framework of the expanded Biggs’ 3P model. Some of the notable findings include: (1) the indirect effects of personality traits -conscientiousness and openness on academic performance; (2) the negative effect of a high level of personality trait agreeableness on academic performance; (3) intrinsic motivation as a key mediator in most of the significant indirect effects as well as being an important independent construct; and (4) the direct effects of personality traits (in particular, agreeableness and openness) on students’ perceptions of the course. The insights gained from this study could provide universities with valuable information for designing more effective student support and interventions.